Doctrinal interpretations of digitalisation as a general legal phenomenon - Emin Najafli (Bulletin of Kharkiv National University of Internal Affairs)
The article demonstrates the doctrinal interpretations of digitalisation as a general legal phenomenon. The emphasis is placed on the fact that the analysis of the content of scientific publications in the field of digitalisation of social relations indicates that priority in this area is still given to highly specialised issues which are studied mainly within the framework of branch legal sciences, primarily constitutional, judicial, administrative and civil law. Therefore, the study of digitalisation usually lacks a comprehensive nature, since the relevant issues are analysed without clarifying the conceptual basis of digitalisation. The approaches proposed in the national legal science to improve certain legal regulators and reorient legislation to regulate social relations in the field of digitalisation often fall behind the rapid development of the relevant processes.